Use of diffusive gradients in thin films and tangential flow ultrafiltration for fractionation of Al(III) and Cu(II) in organic-rich river waters - Tonello, Paulo S.; Rosa, Andre H.; Abreu, Cassio H.; Menegario, Amauri A. (Elsevier B.V., 2007)
Diffusive gradients in thin films (DGT) and tangential-flow ultrafiltration (TF-UF) were combined for fractionation of Al and Cu in river water containing high content of dissolved organic carbon. A procedure based on ultrafiltration data is proposed to determine diffusion coefficients of the analytes in water samples and model solutions containing both free metal (M) and complex (metal - humic substance). Aiming to evaluate the accuracy of the proposed approach, the DGT results were compared with those from a protocol for determination of labile Al and Cu based on solid phase extraction (SPE). Good agreement between data from DGT and SPE were attained for model solutions. For analysis of real organic-rich water samples, differences between DGT and SPE measurements were consistent with the time-scales of the techniques. The concentration of labile Al determined by DGT were lower than the total dissolved concentrations (determined by inductively coupled plasma mass spectrometry) and exceeded the ultrafiltered concentration, indicating that inorganic Al species (species small enough to pass through 1 kDa membrane) were minor species as compared with Al organic complexes. For both Al and Cu, there were species not measured by DGT as they are not sufficiently labile. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: diffusive gradients; tangential-flow ultrafiltration; copper; aluminum; humic substances